Amorphous SiBCN ceramic block with high density and excellent oxidation resistance and preparation method of amorphous SiBCN ceramic block

By curing, crushing, ball milling and vacuum pyrolysis, combined with discharge plasma sintering (SPS) method, amorphous SiBCN ceramic blocks with high density and excellent oxidation resistance are prepared, solving the problem that SiBCN ceramic blocks in the prior art are difficult to maintain amorphous structure and insufficient oxidation resistance.

CN119569464AActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411782212.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing SiBCN ceramic blocks are difficult to maintain an amorphous structure and insufficient oxidation resistance during the preparation process, resulting in low material density, many pores, and difficult size control, which cannot meet the needs of high performance and large size.

Method used

After curing with polyborosilazane, amorphous SiBCN ceramic powder was obtained by pulverizing, ball milling and vacuum pyrolysis, and amorphous SiBCN ceramic bulk was prepared by discharge plasma sintering (SPS).

Benefits of technology

Amorphous SiBCN ceramic blocks with high density, low pore defects, adjustable size, small shrinkage and excellent anti-oxidation properties are achieved, which meets the needs of large size, high quality and high performance, and solves the problems of limited material size and many pores during the preparation of traditional SiBCN ceramic blocks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569464A_ABST
    Figure CN119569464A_ABST
Patent Text Reader

Abstract

The invention relates to an amorphous SiBCN ceramic block with high density and excellent oxidation resistance and a preparation method of the amorphous SiBCN ceramic block, and belongs to the technical field of high-performance ceramic materials.The preparation method of the amorphous SiBCN ceramic block comprises the steps that after polyborosilazane is cured, smashing, ball milling and vacuum pyrolysis are conducted, and amorphous SiBCN ceramic powder is obtained; and carrying out spark plasma sintering on the amorphous SiBCN ceramic powder to obtain the amorphous SiBCN ceramic block. The preparation method of the amorphous SiBCN ceramic block provided by the invention can be used for preparing the amorphous SiBCN ceramic block with high density, low pore defect, adjustable size, small shrinkage rate and excellent oxidation resistance, and can effectively solve the problems of limited material size, more pores and the like in the traditional preparation process of the SiBCN ceramic block.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance ceramic materials, and in particular to an amorphous SiBCN ceramic block with high density and excellent oxidation resistance and a preparation method thereof. Background Art

[0002] SiBCN ceramics have shown broad application potential in the field of high-temperature structural materials due to their excellent high-temperature stability, outstanding oxidation resistance, excellent mechanical properties and low thermal expansion coefficient, and have become the focus of many high-tech fields. In the actual preparation of large, dense ceramic blocks, there are two main challenges: one is that it is difficult to maintain its amorphous structure while achieving material densification; the other is that the oxidation resistance needs to be further improved. In addition, traditional preparation methods are limited by the process, which often leads to more pores inside the material, difficulty in size control, and the oxidation resistance is difficult to meet higher requirements for application scenarios. Summary of the invention

[0003] In response to one or more technical problems existing in the prior art, the present invention provides an amorphous SiBCN ceramic block with high density and excellent antioxidant properties and a preparation method thereof. The preparation method of the amorphous SiBCN ceramic block provided by the present invention can obtain an amorphous SiBCN ceramic block with high density, low pore defects, adjustable size, small shrinkage and excellent antioxidant properties, which can meet the preparation needs of large-size, high-quality and high-performance amorphous SiBCN ceramic blocks, and effectively solve the problems of limited material size and many pores in the preparation process of traditional SiBCN ceramic blocks.

[0004] In a first aspect, the present invention provides a method for preparing an amorphous SiBCN ceramic block having high density and excellent oxidation resistance, the preparation method comprising:

[0005] After the polyborosilazane is solidified, it is crushed, ball-milled, and vacuum-pyrolyzed to obtain amorphous SiBCN ceramic powder;

[0006] The amorphous SiBCN ceramic powder is subjected to spark plasma sintering to obtain an amorphous SiBCN ceramic block.

[0007] Preferably, the curing is carried out under vacuum conditions, the curing temperature is 300-350° C., and the curing time is 2-4 hours.

[0008] Preferably, the heating rate during the curing process is 0.5-1.5°C / min.

[0009] Preferably, the mass ratio of ball material to water during the ball milling process is 2-4:1:1.5-3, the ball milling speed is 200-400 rpm, and the ball milling time is 4-12 h.

[0010] Preferably, the particle size of the amorphous SiBCN ceramic powder is less than 75 μm.

[0011] Preferably, the vacuum pyrolysis is carried out at a temperature of 1000 to 1400° C. and for a time of 2 to 6 hours.

[0012] Preferably, the heating rate of the vacuum pyrolysis process is 1-3°C / min.

[0013] Preferably, the spark plasma sintering is carried out in an inert atmosphere, the sintering temperature is 1400-1600° C., the sintering pressure is 30-60 MPa, and the sintering time is 3-15 min.

[0014] In a second aspect, the present invention provides an amorphous SiBCN ceramic block with high density and excellent oxidation resistance, which is prepared by the preparation method described in the first aspect.

[0015] Preferably, the density of the amorphous SiBCN ceramic block is greater than 2.2 g / cm 3 , porosity is less than 3.5%.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects:

[0017] The present invention can effectively increase the content of B element in the amorphous SiBCN ceramic powder after pyrolysis and reduce the content of N element by subjecting the obtained amorphous SiBCN ceramic powder to vacuum pyrolysis, and can inhibit the thermal reduction reaction, thereby improving the oxidation resistance of the material. The amorphous SiBCN ceramic powder after vacuum pyrolysis is used to prepare an amorphous SiBCN ceramic block by spark plasma sintering (SPS), which can ensure that the oxidation resistance of the material is significantly improved while maintaining the amorphous structure of the material, and obtain an amorphous SiBCN ceramic block with high density, low pore defects, adjustable size, small shrinkage rate and excellent oxidation resistance, which can meet the preparation requirements of large-size, high-quality and high-performance amorphous SiBCN ceramic blocks, and effectively solve the problems of limited material size and many pores in the preparation process of traditional SiBCN ceramic blocks.

[0018] The amorphous SiBCN ceramic block provided by the present invention has high density, low pore defects, adjustable size, small shrinkage and excellent oxidation resistance, and can meet the use requirements of ultra-high temperature fields such as aerospace and high-temperature structural materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 It is a comparison chart of the oxidation thermogravimetric results of the amorphous SiBCN ceramic powder after vacuum pyrolysis of Example 1 of the present invention and the amorphous SiBCN ceramic powder after argon pyrolysis of Comparative Example 3;

[0021] Figure 2 is the XRD spectrum of the amorphous SiBCN ceramic block prepared in Example 1 of the present invention;

[0022] Figure 3 These are macroscopic and microscopic images of the amorphous SiBCN ceramic block obtained in Example 1 of the present invention;

[0023] Figure 4 These are macroscopic and microscopic images of the amorphous SiBCN ceramic block prepared in Comparative Example 1 of the present invention;

[0024] Figure 5 These are macroscopic and microscopic images of the amorphous SiBCN ceramic block obtained in Comparative Example 2 of the present invention;

[0025] Figure 6 This is a graph showing the results of the oxidation resistance test (temperature of 1400° C. and time of 2 h) of the amorphous SiBCN ceramic blocks prepared in Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In a first aspect, the present invention provides a method for preparing an amorphous SiBCN ceramic block having high density and excellent oxidation resistance, the preparation method comprising:

[0028] After the polyborosilazane is solidified, it is crushed, ball-milled, and vacuum-pyrolyzed to obtain amorphous SiBCN ceramic powder;

[0029] The amorphous SiBCN ceramic powder is subjected to spark plasma sintering to obtain an amorphous SiBCN ceramic block.

[0030] The present invention can effectively increase the content of B element in the amorphous SiBCN ceramic powder after pyrolysis and reduce the content of N element by subjecting the obtained amorphous SiBCN ceramic powder to vacuum pyrolysis, and can inhibit the thermal reduction reaction, thereby improving the oxidation resistance of the material. The amorphous SiBCN ceramic powder after vacuum pyrolysis is used to prepare an amorphous SiBCN ceramic block by spark plasma sintering (SPS), which can ensure that the oxidation resistance of the material is significantly improved while maintaining the amorphous structure of the material, and obtain an amorphous SiBCN ceramic block with high density, low pore defects, adjustable size, small shrinkage rate and excellent oxidation resistance, which can meet the preparation requirements of large-size, high-quality and high-performance amorphous SiBCN ceramic blocks, and effectively solve the problems of limited material size and many pores in the preparation process of traditional SiBCN ceramic blocks.

[0031] According to some preferred embodiments, the curing is performed under vacuum conditions, the curing temperature is 300-350° C., and the curing time is 2-4 hours.

[0032] According to some preferred embodiments, the heating rate of the curing process is 0.5-1.5°C / min.

[0033] According to some preferred embodiments, the mass ratio of ball material to water during the ball milling process is 2-4:1:1.5-3, the ball milling speed is 200-400 rpm, and the ball milling time is 4-12 h.

[0034] According to some preferred embodiments, the particle size of the amorphous SiBCN ceramic powder is less than 75 μm.

[0035] According to some preferred embodiments, the vacuum pyrolysis is carried out at a temperature of 1000 to 1400° C. and for a time of 2 to 6 hours.

[0036] According to some preferred embodiments, the heating rate of the vacuum pyrolysis process is 1-3°C / min.

[0037] According to some preferred embodiments, the spark plasma sintering is performed in an inert atmosphere, the sintering temperature is 1400-1600° C., the sintering pressure is 30-60 MPa, and the sintering time is 3-15 min.

[0038] In a second aspect, the present invention provides an amorphous SiBCN ceramic block with high density and excellent oxidation resistance, which is prepared by the preparation method described in the first aspect.

[0039] The amorphous SiBCN ceramic block provided by the present invention has high density, low pore defects, adjustable size, small shrinkage and excellent oxidation resistance, and can meet the use requirements of ultra-high temperature fields such as aerospace and high-temperature structural materials.

[0040] According to some preferred embodiments, the density of the amorphous SiBCN ceramic block is greater than 2.2 g / cm 3 , porosity is less than 3.5%.

[0041] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0042] Example 1

[0043] S1. Pour polyborosilazane (PSNB, liquid) into a ceramic boat, and then transfer it to a vacuum curing box for curing, wherein the curing temperature is 350°C, the curing time is 2h, and the heating rate during the curing process is 1°C / min; the block obtained after curing is crushed by a pulverizer, and then ball milled using a planetary ball mill, wherein the mass ratio of ball material to water during the ball milling process is 3:1:2, the ball milling speed is 300rpm, the ball milling time is 10h, and it is sieved through a 200-mesh sieve, and then the cured powder is transferred to a high-temperature tubular furnace and pyrolyzed under vacuum conditions, wherein the pyrolysis temperature is 1000°C, the time is 4h, and the heating rate during the pyrolysis process is 1°C / min, to obtain amorphous SiBCN ceramic powder;

[0044] S2. Take 5 g of the amorphous SiBCN ceramic powder after vacuum pyrolysis obtained in step S1, transfer it to a graphite mold, and use spark plasma sintering under an inert atmosphere. The temperature during the spark plasma sintering process is 1500°C, the pressure is 45 MPa, the time is 5 min, and the heating rate is 100°C / min to obtain an amorphous SiBCN ceramic block.

[0045] Comparative Example 1

[0046] Amorphous SiBCN ceramic blocks are prepared using the traditional PDC liquid phase molding method:

[0047] S1. Drop polyborosilazane (PSNB, liquid) into a polytetrafluoroethylene mold, then transfer it to a vacuum curing box, evacuate the air dissolved in the liquid phase, and keep it at 220°C for 2 hours for preliminary curing. Take out the sample after preliminary curing, transfer it to a high-temperature tube furnace, and keep it at 350°C for 2 hours for full curing to obtain a cured sample;

[0048] S2. The solidified sample obtained in S1 was pyrolyzed at 1000°C for 2 hours. The whole process was carried out in flowing argon gas with a heating rate of 0.5-2°C / min to obtain an amorphous SiBCN ceramic block.

[0049] The inventors found that although the material obtained by this method is dense, only thin small discs (thickness <2mm) can be prepared. Once the thickness is increased, it will crack during the pyrolysis process.

[0050] Comparative Example 2

[0051] Amorphous SiBCN ceramic blocks are prepared using the traditional PDC powder molding method:

[0052] S1. Pour polyborosilazane (PSNB, liquid) into a ceramic boat, and then transfer it to a vacuum curing box for curing, wherein the curing temperature is 300-350°C, the curing time is 2-4h, and the heating rate during the curing process is 1°C / min; the block obtained after curing is crushed by a pulverizer, and then ball milled using a planetary ball mill, wherein the mass ratio of ball material to water during the ball milling process is 3:1:2, the ball milling speed is 300rpm, the ball milling time is 10h, and passed through a 200-mesh sieve to obtain a solidified powder;

[0053] S2. The solidified powder and the polyborosilazane precursor (10 wt% of the solidified powder) were mixed evenly in a mortar, and then transferred to a stainless steel mold and pressed into a block using a hot press. The hot press was pressed at a pressure of 350 MPa, a temperature of 80 ° C, and a time of 30 min;

[0054] S3. The green body obtained in step S2 is transferred to a high-temperature tube furnace, and high-temperature pyrolysis is performed under a flowing argon atmosphere to obtain an amorphous SiBCN ceramic block; wherein the heating rate during the high-temperature pyrolysis process is 2°C / min, the high-temperature pyrolysis temperature is 1000°C, and the high-temperature pyrolysis time is 2h.

[0055] The inventors found that the size shrinkage rate after pyrolysis by this method is 25%, and the density is low and the porosity is large.

[0056] Comparative Example 3

[0057] The method is basically the same as Example 1, except that the pyrolysis is performed under an argon atmosphere in step S1.

[0058] Comparative Example 4

[0059] The method is basically the same as Example 1, except that the solidified powder is not pyrolyzed under vacuum conditions, but is directly subjected to spark plasma sintering.

[0060] The inventors found that the sintering process of the method resulted in serious dimensional shrinkage.

[0061] The present invention analyzes the elemental composition of the amorphous SiBCN ceramic powder after vacuum pyrolysis of Example 1 and the amorphous SiBCN ceramic powder after argon pyrolysis of Comparative Example 3, as shown in Table 1.

[0062] Table 1. Elemental composition of amorphous SiBCN ceramic powders after vacuum pyrolysis and argon pyrolysis

[0063]

[0064] As shown in Table 1, compared with the amorphous SiBCN ceramic powder after argon pyrolysis, the content of B element in the amorphous SiBCN ceramic powder after vacuum pyrolysis is significantly increased, which can increase the oxidation resistance; the content of N element is significantly reduced, which can reduce the thermal reduction reaction. It can be seen that the use of vacuum pyrolysis can improve the oxidation resistance of SiBCN ceramics.

[0065] The present invention performs oxidation thermogravimetric experiments on the amorphous SiBCN ceramic powder after vacuum pyrolysis of Example 1 and the amorphous SiBCN ceramic powder after argon pyrolysis of Comparative Example 3 in a mass spectrometer (room temperature -1500°C, flowing air). The oxidation thermogravimetric results are compared with Figure 1 As shown, the results show that the mass change of the amorphous SiBCN ceramic powder after vacuum pyrolysis of Example 1 is small during the whole oxidation process, and the maximum mass loss is only 0.4%, while the maximum mass loss of the amorphous SiBCN ceramic powder after argon pyrolysis of Comparative Example 3 is 1.8% during the whole oxidation process. It can be seen that the anti-oxidation performance of the SiBCN ceramic powder after vacuum pyrolysis of Example 1 is significantly better than that of the amorphous SiBCN ceramic powder after argon pyrolysis of Comparative Example 3.

[0066] Depend on Figure 2 It can be seen that the XRD spectrum of the amorphous SiBCN ceramic block prepared in Example 1 has no obvious peaks, proving that the prepared SiBCN ceramic block is amorphous.

[0067] Depend on Figure 3 It can be seen that the amorphous SiBCN ceramic block (diameter 25 mm, thickness 4 mm) prepared in Example 1 has a uniform structure, no obvious pores and cracks in the microstructure, low porosity and high density. The porosity of the amorphous SiBCN ceramic block prepared in Example 1 is 3.46% and the density is 2.24 g / cm 3 .

[0068] Depend on Figure 4 It can be seen that the amorphous SiBCN ceramic block prepared in Comparative Example 1 has high density, low porosity, uniform microstructure, no obvious pores and cracks, but small size (thickness <2mm); during the preparation process, the size shrinks severely from the solidified state to the pyrolysis state. It is measured that the porosity of the amorphous SiBCN ceramic block prepared in Comparative Example 1 is 1.5%, and the density is 2.01g / cm 3The shrinkage rate from the solidified state to the pyrolyzed state is 22.0%. In addition, the inventors found that the preparation method of Comparative Example 1 can only produce thin small amorphous SiBCN ceramic blocks. Once the size increases, it is easy to crack and break during pyrolysis, and it is impossible to form large and dense amorphous SiBCN ceramic blocks. It should be noted that Figure 4 The solidified state refers to the solidified state sample obtained after step S1 in comparative example 1, and the pyrolysis state refers to the amorphous SiBCN ceramic block obtained after step S2 in comparative example 1.

[0069] Depend on Figure 5 It can be seen that the amorphous SiBCN ceramic block prepared in Comparative Example 2 has low density and large porosity, and there are obvious pores and cracks in the microstructure. In addition, the size shrinks severely from the solidified state to the pyrolysis state during the preparation process. The porosity of the amorphous SiBCN ceramic block prepared in Comparative Example 2 is measured to be 22.8%, and the density is 1.62 g / cm 3 , the dimensional shrinkage from the solidified state to the pyrolyzed state is about 25%. It should be noted that Figure 5 The solidified state refers to the material obtained after step S2 of comparative example 2, and the pyrolysis state refers to the amorphous SiBCN ceramic block obtained after step S3 of comparative example 2.

[0070] Depend on Figure 6 It can be seen that the amorphous SiBCN ceramic blocks obtained by Example 1 and Comparative Example 3 were subjected to an oxidation resistance test in a muffle furnace (temperature of 1400°C, time of 2h). It can be seen that the amorphous SiBCN ceramic block obtained by sintering the SiBCN ceramic powder after argon pyrolysis in Comparative Example 3 was obviously oxidized, and the surface was almost covered with white matter (SiO2), while the amorphous SiBCN ceramic block obtained by sintering the SiBCN ceramic powder by vacuum pyrolysis in Example 1 had only a small amount of white matter. In addition, the mass loss of the amorphous SiBCN ceramic block obtained by Example 1 was about 0.16% before and after the test, and the mass loss of the amorphous SiBCN ceramic block obtained by Comparative Example 3 was about 1.64% before and after the test. It can be seen that the static oxidation resistance of the amorphous SiBCN ceramic block obtained by the vacuum pyrolysis process is significantly better than that of the amorphous SiBCN ceramic block obtained by the vacuum pyrolysis process.

[0071] In summary, the amorphous SiBCN ceramic block prepared by the preparation method of the present invention has high density, low pore defects, adjustable size, small shrinkage and excellent antioxidant properties, which can meet the preparation needs of large-size, high-quality and high-performance amorphous SiBCN ceramic blocks, and effectively solve the problems of limited material size and many pores in the preparation process of traditional SiBCN ceramic blocks.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an amorphous SiBCN ceramic block with high density and excellent oxidation resistance, characterized in that: The preparation method comprises: After the polyborosilazane is solidified, it is crushed, ball-milled, and vacuum-pyrolyzed to obtain amorphous SiBCN ceramic powder; The amorphous SiBCN ceramic powder is subjected to spark plasma sintering to obtain an amorphous SiBCN ceramic block.

2. The preparation method according to claim 1, characterized in that: The curing is carried out under vacuum conditions, the curing temperature is 300-350° C., and the curing time is 2-4 hours.

3. The preparation method according to claim 2, characterized in that: The heating rate of the curing process is 0.5-1.5°C / min.

4. The preparation method according to claim 1, characterized in that: In the ball milling process, the mass ratio of ball material to water is 2-4:1:1.5-3, the ball milling speed is 200-400 rpm, and the ball milling time is 4-12 hours.

5. The preparation method according to claim 1, characterized in that: The particle size of the amorphous SiBCN ceramic powder is less than 75 μm.

6. The preparation method according to claim 1, characterized in that: The vacuum pyrolysis is carried out at a temperature of 1000 to 1400° C. and for a time of 2 to 6 hours.

7. The preparation method according to claim 6, characterized in that: The heating rate of the vacuum pyrolysis process is 1-3°C / min.

8. The preparation method according to claim 1, characterized in that: The spark plasma sintering is carried out in an inert atmosphere, the sintering temperature is 1400-1600° C., the sintering pressure is 30-60 MPa, and the sintering time is 3-15 minutes.

9. An amorphous SiBCN ceramic block with high density and excellent oxidation resistance, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. The amorphous SiBCN ceramic block according to claim 9, characterized in that: The density of the amorphous SiBCN ceramic block is greater than 2.2 g / cm 3 , porosity is less than 3.5%.

Citation Information

Patent Citations

  • Bulk compact amorphous SiBCN ceramic block and preparation method thereof

    CN117902903A

  • Silicon carbide connecting layer material as well as preparation method and application thereof

    CN118206377A

  • A System that collects and manages users' histories with a SaaS platform-based RFID card.

    KR1020220156994A

  • Compressible coating reinforcements for ceramic matrix composites, and methods of making the same

    US11787746B1